Training-induced impairment of endothelial function in track and field female athletes - Marcin Grandys; Joanna Majerczak; Marzena Frolow; Stefan Chlopicki; Jerzy A. Zoladz (Scientific Reports, 2023)
Abstract Professional athletes are often exposed to high training loads that may lead to overfatigue, overreaching and overtraining that might have a detrimental effects on vascular health. We determined the effects of high training stress on endothelial function assessed by the flow-mediated dilation (FMD) and markers of glycocalyx shedding. Vascular examination as well as broad biochemical, hormonal and cardiometabolic evaluation of sprint and middle-distance female runners were performed after 2 months of preparatory training period and compared to age-matched control group of women. Female athletes presented with significantly reduced FMD (p < 0.01) and higher basal serum concentrations of hyaluronan (HA) and syndecan-1 (SDC-1) (p < 0.05 and p < 0.001, respectively), that was accompanied by significantly lower basal serum testosterone (T) and free testosterone (fT) concentrations (p < 0.05) and higher cortisol (C) concentration (p < 0.05). It resulted in significantly lower T/C and fT/C ratios in athletes when compared to controls (p < 0.01). Moreover, fT/C ratio were significantly positively correlated to FMD and negatively to HA concentrations in all studied women. Accordingly, the training load was significantly negatively correlated with T/C, fT/C and FMD and positively with the concentrations of HA and SDC-1. We concluded that young female track and field athletes subjected to physical training developed impairment of endothelial function that was associated with anabolic-catabolic hormone balance disturbances. Given that training-induced impairment of endothelial function may have a detrimental effects on vascular health, endothelial status should be regularly monitored in the time-course of training process to minimalize vascular health-risk in athletes.